Focused Update of Sex Differences in Patient Reported Outcome Measures After Stroke. Issue 3 (March 2018) - Gall, Seana; Phan, Hoang; Madsen, Tracy E.; Reeves, Mathew; Rist, Pamela; Jimenez, Monik; Lichtman, Judith; Dong, Liming; Lisabeth, Lynda D.
Abstract : Supplemental Digital Content is available in the text.